2008
DOI: 10.1016/j.ejcts.2008.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Coronary surgery in patients with diabetes mellitus: a risk-adjusted study on early outcome

Abstract: Despite worse demographic and clinical characteristics, diabetic patients could be surgically revascularized with low mortality and morbidity, comparable with control patients. Hence, our data do not support diabetes as a risk factor for significantly adverse early outcome following CABG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
18
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 22 publications
6
18
0
2
Order By: Relevance
“…Thus, the combination of diabetes with some of these variables can justify its expression as a risk factor. Our observations related to diabetes were similar to other studies that have shown a higher proportion of diabetics in the group with prolonged hospitalization [9,16,18,21], and that this disorder, itself, is a risk factor for prolonged hospitalization [11,13]. However, other studies found no association between diabetes and risk for prolonged hospitalization [6,7,16].…”
Section: Bmi -Body Mass Index; Ef -Ejection Fraction; Oi-sc -Oxygenatsupporting
confidence: 69%
See 1 more Smart Citation
“…Thus, the combination of diabetes with some of these variables can justify its expression as a risk factor. Our observations related to diabetes were similar to other studies that have shown a higher proportion of diabetics in the group with prolonged hospitalization [9,16,18,21], and that this disorder, itself, is a risk factor for prolonged hospitalization [11,13]. However, other studies found no association between diabetes and risk for prolonged hospitalization [6,7,16].…”
Section: Bmi -Body Mass Index; Ef -Ejection Fraction; Oi-sc -Oxygenatsupporting
confidence: 69%
“…These observations support the fact that diabetes per se, is a risk factor for coronary heart disease [1,18] and its more severe degree [19]. Furthermore, diabetes is associated with a greater number of surgical complications such as perioperative myocardial infarction [20], prolonged MV [20], infection [18] and cerebrovascular accidents [18], which prolongs the ICU. Also, the use of CPB worsens glycemic control, may increase the frequency of these complications [20].…”
Section: Bmi -Body Mass Index; Ef -Ejection Fraction; Oi-sc -Oxygenatsupporting
confidence: 59%
“…18 Literature suggests that diabetes has been an independent risk factor for development of stroke in patients undergoing CABG. 30 In accordance to this, various studies also favour PCI with DES over CABG in terms of occurrence of cerebrovascular events in such patients (OR [95%CI] = 2.15[0.99-4.68]). 24 Additionally, a prospective study has reported that 42% of patients who underwent CABG have subtle cognitive impairment 5 years after surgery.…”
Section: Resultsmentioning
confidence: 77%
“…1 Compared with nondiabetic individuals, diabetic patients undergoing coronary artery bypass grafting (CABG) have worse outcomes, including higher mortality, and higher rates of morbidity in the forms of deep sternal instability, wound infection, stroke, renal dysfunction, and respiratory problems. [2][3][4][5][6] Moreover, longer intensive care unit and hospital stays, poorer postoperative physical functioning, and lower quality of life are evident. [2][3][4][5][6] Nonetheless, CABG is preferred over percutaneous coronary intervention (PCI) in patients undergoing diabetes treatment.…”
mentioning
confidence: 98%
“…[2][3][4][5][6] Moreover, longer intensive care unit and hospital stays, poorer postoperative physical functioning, and lower quality of life are evident. [2][3][4][5][6] Nonetheless, CABG is preferred over percutaneous coronary intervention (PCI) in patients undergoing diabetes treatment. 7,8 With demographic changes resulting in an increase of the elderly population, the incidence of diabetes mellitus is also expected to increase, as is the number of CABG surgeries.…”
mentioning
confidence: 98%